Variability in almond oil chemical traits from traditional cultivars and native genetic resources from Argentina. (1st March 2015) - Maestri, Damián; Martínez, Marcela; Bodoira, Romina; Rossi, Yanina; Oviedo, Alejandro; Pierantozzi, Pierluigi; Torres, Mariela
Highlights: Traditional and new almond genotypes were analysed in oil content and composition. High variability was found for oil, fatty acids, α-tocopherol and squalene contents. The genotype was the main variability source for all these chemical traits. Almond genotypes native from Argentina had the highest oil and oleic acid contents. Results contribute to breeding focused to select almond cultivars for oil production. Abstract: Almond ( Prunus dulcis (Miller) D.A. Webb) genetic resources (Marcona, Guara, Non Pareil, IXL, AI, Martinelli C, Emilito INTA, Cáceres Clara Chica, Javier INTA) were studied during two consecutive crop years in order to evaluate variations in kernel oil yield and composition, and oil oxidative parameters. Total oil, oleic acid, α-tocopherol and squalene contents were found to range between 48.0% and 57.5%, 65% and 77.5%, 370 and 675 μg/g oil, and 37.9 and 114.2 μg/g oil, respectively. The genotype was the main variability source for all these chemical traits. The α-tocopherol content seems to be the most important contributor to both the radical scavenging capacity and the oxidative stability of almond oils analysed. Results obtained from the local genotypes namely Martinelli C, Emilito INTA and Javier INTA may be of interest for almond breeding focused to improve kernel oil yield and composition.